Field Evaluation of Different Attractants for Detecting and Monitoring Drosophila suzukii - Larson, Nicholas R.; Strickland, Jaime; Shields, Vonnie D.; Rodriguez-Saona, Cesar; Cloonan, Kevin; Short, Brent D.; Leskey, Tracy C.; Zhang, Aijun (Frontiers in Ecology and Evolution, 2021)
Drosophila suzukii (Matsumura), more commonly known as the spotted-wing drosophila (SWD), is an invasive pest of soft, thin-skinned fruit responsible for significant economic losses for farmers and growers worldwide. To improve detection methods, several lures have been developed for use in trapping SWD, however, they lack selectivity. Therefore, there is a significant need for more selective monitoring devices to enable growers to make timely pest management decisions to properly protect vulnerable crops. Previous studies identified a quinary blend (QB) that offers significantly higher selectivity by increasing SWD captures while reducing non-target captures, compared with the standard apple cider vinegar bait. In this study, the selectivity and efficacy of the QB was compared to two commercially available (Scentry and Trécé) SWD lures across blueberry and raspberry fields in Maryland, West Virginia, and New Jersey. A formulated version of the QB consistently had higher selectivity within the blueberry and raspberry field sites compared with commercial lures; although efficacy was compromised such that total SWD captures per trap tended to be lower. The selectivity ratio range of SWD to non-targets for a QB-based (ChemTica) lure averaged 15-57% compared with other commercial lures that ranged from 1-30%. Due to high selectivity of the formulated version of the QB, the potential for this lure to be utilized by growers as a SWD monitoring tool is high.